2020
DOI: 10.1149/1945-7111/ab904f
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Leakage Current in Proton-Conducting BaZr0.8Y0.2O3−δ Electrolyte by Forming Hole-Blocking Layer

Abstract: Solid oxide fuel cells (SOFCs) with proton-conducting solid electrolyte, instead of the oxide-ion conducting solid electrolyte have attracted attentions because of their high potential to reduce operating temperatures and to enhance the electrical efficiencies of SOFCs. In addition, the proton-conducting SOFCs with multistage electrochemical oxidation configuration will be promising technology for critically-high electric efficiencies. However, it is known that there are non-negligible charge -carriers other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Another widely proposed approach for decreasing electron leakage in electrolytes presented in the literature consists in the formation of the so-called blocking layers. However, since this strategy has been thoroughly discussed in a number of research works 187–200 and reviews 42,43,201 it is considered to be beyond the scope of the present overview.…”
Section: Concluding Remarks and Further Prospectsmentioning
confidence: 99%
“…Another widely proposed approach for decreasing electron leakage in electrolytes presented in the literature consists in the formation of the so-called blocking layers. However, since this strategy has been thoroughly discussed in a number of research works 187–200 and reviews 42,43,201 it is considered to be beyond the scope of the present overview.…”
Section: Concluding Remarks and Further Prospectsmentioning
confidence: 99%
“…In the bilayer model, terminal voltage (V T ), can be calculated from the following equations. 11) e;i ) of the electrolyte "i". The subscript "i" expresses BZY when i = 1 and LWO when i = 2.…”
Section: Theoretical Estimation Of Cell Performancementioning
confidence: 99%
“…This characteristic transport property of LWO motivates us to apply LWO to a hole-blocking layer for the PCFCs. 11) The holeblocking layer is a thin proton-conducting layer with low hole conductivity fabricated on the cathode side of a thicker electrolyte membrane to suppress the leakage current arising from the hole conduction in the electrolyte membrane. Our previous theoretical calculations suggested that the leakage current in a BaZr 0.8 Y 0.2 O 3¹¤ (BZY) electrolyte membrane can be well suppressed by introducing a thin LWO hole-blocking layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a leakage current through the electrolyte membrane derived from non-negligible hole conduction in the protonconducting electrolyte causes a reduction of open-circuit voltage and energy efficiency of the cell. 22,23 Since the energy gap between the valance band maximum (VBM) and the acceptor level dominates hole concentration in the proton-conducting oxides, determination of the position of the acceptor level and that of the VBM can contribute to the development of the proton-conducting oxides for highefficiency PCFCs. While previously reported optical measurements using powder samples and single crystals with a thickness of several tens to several hundred micrometers have advantages for detecting the weak defect-related optical absorption, 18,20,24 direct determination of a fundamental absorption edge derived from the excitation of electrons from the valence band (VB) to the conduction band (CB) having large absorption coefficient α is difficult when such a thick specimen are used because large α results in a quite small transmittance or small diffuse reflectance below a detection limit.…”
Section: Introductionmentioning
confidence: 99%